Potential Soil Loss Rates in Urualla Nigeria using Rusle (Global Journal of Science Frontier Research, 2018)
Soil erosion represents a natural risk which produces material and human losses annually. The assessment and mapping of erosion prone areas are essential for soil watershed management. The objective was to apply RUSLE model to determine the amount of soil loss in Urualla watershed of Imo, Nigeria. Land use and land cover map was obtained from Google earth satellite image; ground control point data was collected from GeoSmart Survey, Imo State, Nigeria; 25 years- annual rainfall data was obtained from NIMET; soil map was generated from Onyekanne et al. (2012) soil data. The various components of RUSLE were integrated into the ArcGIS 10.2.1 to estimate the annual soil loss in the area. The soil loss in the area ranged from 6 to 1200 t/ha/year while the mean annual soil loss is 36 t/ha/yr. The erosion map obtained shows that in the study area, 25.9% has medium erosion rate of 10-15 t/ha/yr; 33.6% has moderately high erosion rate of 15-25 t/ha/yr; 16.4% has high rate of 25-50 t/ha/yr while 14.7% has a rate greater than 50 t/ha/yr. The study shows that GIS presents simple and low cost tools for assessing erosion potential and risk in a watershed.
Keywords: soil erosion; GIS; RUSLE; urualla watershed; map; erosion factors